2005
DOI: 10.1111/j.1399-3038.2005.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of heat‐killed Lactobacillus paracasei for treatment of perennial allergic rhinitis induced by house‐dust mite

Abstract: Live Lactobacillus paracasi 33 (LP33) may effectively improve the quality of life for patients with perennial allergic rhinitis. It has been demonstrated that heat-killed lactic acid bacteria (LAB) suppress specific immunoglobulin E synthesis and stimulate interleukin-12 production in animals. The aim of this study was, therefore, to evaluate the efficacy of heat-killed LP33 in the treatment of allergic rhinitis induced by house-dust-mite in human subjects. A total of 90 patients were enrolled in a randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
129
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 19 publications
0
129
0
2
Order By: Relevance
“…Some controlled trials reported overall positive results with the administration of lactobacillus in children with AR [108,109], and a small study reported clinical and anti-inflammatory effects provided by Bacillus clausii [110]. Data showing that probiotic supplementation modulates immune responses in AR and may potentially alleviate the AR symptom severity [111] are encouraging, but their primary preventive effect on atopic diseases, probably by enhancing the T helper type 1 (TH1) response, is still unconfirmed [112].…”
Section: Other Interventionsmentioning
confidence: 98%
“…Some controlled trials reported overall positive results with the administration of lactobacillus in children with AR [108,109], and a small study reported clinical and anti-inflammatory effects provided by Bacillus clausii [110]. Data showing that probiotic supplementation modulates immune responses in AR and may potentially alleviate the AR symptom severity [111] are encouraging, but their primary preventive effect on atopic diseases, probably by enhancing the T helper type 1 (TH1) response, is still unconfirmed [112].…”
Section: Other Interventionsmentioning
confidence: 98%
“…The organisms were lyophilized and suspended in PBS at 10 mg/ml and then killed by heating the solution to 100°C for 30 min. The stock suspensions which contained approximately 2ϫ10 10 , 1ϫ10 10 , and 3ϫ10 10 cells/ml for M-16V, LGG and STH, respectively, The Bifidobacterium breve M-16V strain has previously been shown to be effective in infants in improving the symptoms of allergic hypersensitivity to cow's milk and atopic dermatitis. In the current study, we investigated the effect of an oral administration of M-16V on immunoglobulin (Ig) E production in BALB/c mice.…”
Section: Mice and Bacteriamentioning
confidence: 99%
“…In numerous human trials, the intake of probiotics, such as lactobacilli and bifidobacteria, has been reported to prevent several allergic diseases. [6][7][8][9][10][11] The potential benefit of probiotic bacteria in the modulation and regulation of the immune response has also been reported in both in vitro and in animal studies. [12][13][14][15][16][17][18][19] Bifidobacterium breve M-16V is a probiotic strain that was isolated from fecal sample of a healthy baby.…”
mentioning
confidence: 99%
“…9) Moreover, it has been proposed that DCs localized in the gut-associated lymphoid tissue can sample bacteria directly from the intestinal lumen and modify the immune homeostasis. 10) Clinical studies conducted in humans have indicated that LAB can alleviate the symptoms of atopy [11][12][13][14] and perennial allergic rhinitis [15][16][17] and enhance the anti-carcinogenic activity of the immune system. [18][19][20][21] Since the bacterial properties required for the different applications are clearly distinct, selection of the LAB strain is very important for a more rational use of these organisms.…”
mentioning
confidence: 99%